Internalization and Actualization of Larap Slambu Cultural Character Values in Elementary School Students - Umi Sholichah; Mintasih Indriayu; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2024)
The moral crisis that often occurs in elementary schools can be overcome by strengthening character education. Strengthening character education can be taken from the culture surrounding society, one of which is the larap slambu culture. The aim of this research is to determine the process of internalization and actualization of character values based on the larap slambu culture based on the strategies implemented by classroom teachers of elementary school students. This research uses qualitative ethnographic study methods. The data analysis technique used is analysis, description, and summary of phenomena based on data obtained through interviews and observation. The results of the research show that the cultural character values of Larap Slambu are religious values, democratic values, environmental care values, social care values, and responsibility values. The results of this research provide recommendations that educators and stakeholders need to realize the importance of internalizing and actualizing local cultural character values. This aims to improve student character and encourage the use of local culture as a model for strengthening student character in various regions.